2014
DOI: 10.1155/2014/873525
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-nonenal Induces Apoptosis by Inhibiting AKT Signaling in Human Osteosarcoma Cells

Abstract: The onset of lipid peroxidation within cellular membranes is associated with changes in their physiochemical properties and enzymatic dysfunction of the membrane environment. There are increasing bodies of evidence indicating that aldehydic molecules generated endogenously during the process of lipid peroxidation are causally involved in most of the pathophysiological effects associated with oxidative stress in cells and tissues. 4-Hydroxy-2-nonenal (4-HNE), among them, is believed to be largely responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Immunohistochemical staining of HNE adducts was demonstrated in animal models of liver cancer [110]. HNE treatment of MG63 human osteosarcoma cells could activate caspase-3 and altered the Bax/Bcl-2 ratio, thereby inducing cell death [111]. A recent research showed that HNE increased the growth of breast cancer cells and promoted their angiogenesis and invasion [112].…”
Section: Poducts Of Lipid Peroxidation As Common Markers Of Oxidativementioning
confidence: 99%
“…Immunohistochemical staining of HNE adducts was demonstrated in animal models of liver cancer [110]. HNE treatment of MG63 human osteosarcoma cells could activate caspase-3 and altered the Bax/Bcl-2 ratio, thereby inducing cell death [111]. A recent research showed that HNE increased the growth of breast cancer cells and promoted their angiogenesis and invasion [112].…”
Section: Poducts Of Lipid Peroxidation As Common Markers Of Oxidativementioning
confidence: 99%
“…4-HNE may also interact with other proteins; for example, it forms adducts with His196, His267, Cys311, and Ser473 residues of AKT kinase, which results in a reduction in AKT sensitivity to phosphorylation. Additionally, modification of Ser473, considered to be the primary AKT regulatory site, leads to a decrease in the activity of the protein [56,57]. Because AKT has antiapoptotic effects through inhibiting several proapoptotic factors (including Acinus, AKS1, Bad, Bax, caspase-9) and activating antiapoptotic proteins (CREB and IKKα), suppression of AKT activity leads to a significant increase in apoptosis.…”
Section: Ros-dependent Lipid Peroxidation Productsmentioning
confidence: 99%
“…HNE decreased AKT phosphorylation and activity in a wide concentration range from 5–100 μM in MG63 human osteosarcoma cells [77], 3T3-L1 adipocytes [78], human OA chondrocytes [79] and Jurkat cells [80]. In contrast, increased AKT phosphorylation was observed in vascular smooth muscle cells (1μM) [50], PC12 cells (15 μM) [81], human neuroblastoma IMR-32 cells (10 μM) [82], human corneal epithelial cells (30μM) [83] and retinal pigment epithelial (RPE) cells (0.1–5 μM) [84].…”
Section: Aging-related Signaling Pathways Affected By Hnementioning
confidence: 99%